Spectrally resolved nonlinear optical properties of doped versus undoped quasi-2D semiconductor nanocrystals : copper and silver doping provokes strong nonlinearity in colloidal CdSe nanoplatelets - Nawrot, Katarzyna C. (2022)
Nonlinear optical processes are crucial for emerging applications including multiphoton-excited fluorescence microscopy and optical power limiting. Therefore, searching for materials of high multiphoton absorption cross sections is essential for the development of these techniques. We present synthesis of 4.5 monolayer CdSe nanoplatelets (NPLs) doped with silver and copper ions along with the evaluation of their two-photon absorption (TPA) and three-photon absorption (3PA) cross sections. Doping significantly increases the TPA cross section of each NPL sample, which reaches up to 1.33 × 107 GM for the most absorbing copper-doped ones. We also detected 1-2 orders of magnitude-enhanced 3PA cross sections for the doped NPLs in comparison with their undoped counterparts. As TPA and 3PA peaks appear, in the first and the second biological transmission windows, respectively, doped NPLs are promising candidates for multiphoton fluorescence microscopy as bioimaging agents. Moreover, the strong nonlinear response suggests application as active optoelectronic materials in optical sensors.